Design and Shape Optimization of Blade Profile and support-arms for Small Scale Vertical Axis Wind Turbine - Van Stratan, Gavin Scott Manggai (Curtin University, 2023)
In this thesis, blade shape optimization of a vertical axis wind turbine blade was performed. The study consist of 2D and 3D analysis using computational fluid dynamics. 2D shape optimization was performed on a NACA0018 blade using the adjoint solver together with the gradient based optimizer. An original blade design was obtained, which showed significant performance improvement over the baseline turbine both in 2D and 3D numerical simulation as well as in an experimental study.